Energy Spectrum of the March 1989 Forbush Decrease - Alania, Eteri M.; Bochorishvili, Tengiz B.; Aslamazashvili, Revaz G.; Bakradze, Teimuraz S.; Glonti, Nugzar Ya.; Erkomaishvili, Tereza G.; Belov, Anatoly V.; Yanke, Victor G.; Gushchina, Raisa T.; Eroshenko, Evguenia A.; et al. (Journals of Georgian Geophysical Society, 2025)
Energy Spectrum of the Primary Cosmic Rays based on the experimental data of the World Wide Network of the Neutron Component of the Galactic Cosmic Rays, during the Huge Forbush Decrease of the March 1989 was calculated.